Patient characteristics in tardive COVID‐19 pseudoperniosis: a case series of 16 patients. (1st February 2022) - Ganatra, B.; Amarnani, R.; Alfallouji, Y.; Dear, K.; Twigg, E.; Westwood, J. P.; Goulden, B.; Morris, V.; Hillman, T.; Goolamali, S.; Naderi, Z.; Sidwell, R.; et al.
Summary: Background Acute pseudoperniosis (PP) has a recognized association with COVID‐19 and tends to occur without cold precipitation in young, healthy patients, often without a clear history of COVID‐19. These lesions usually resolve within 2 weeks and without long‐term sequelae. In the early months of 2021, patients with delayed and protracted PP began to emerge. We have called this presentation 'tardive COVID‐19 PP (TCPP)'. Aim To consolidate and expand knowledge on TCPP, we describe the clinical characteristics, treatments and outcomes of 16 patients with TCPP who were reviewed by our outpatient dermatology service. Results The initial clinical manifestations were erythema, swelling and PP of the fingers in 56.2%, and of the toes in 31.2%, desquamation in 56.2% and acrocyanosis in 12.5%. Ten patients had eventual involvement of all acral sites. The median duration of symptoms was 191 days. Six patients reported close contact with a confirmed or suspected case of COVID‐19, but only two had positive COVID‐19 tests. Four patients experienced complete or almost complete resolution of symptoms, while the rest remain under active treatment. Conclusion Unlike acute PP, TCPP has a protracted and delayed presentation that is typically associated with profound acrocyanosis. Patients with TCPP represent a new phenomenon that is part of the post‐COVID‐19 syndrome, with risk factors and pathophysiology that are not yet fully understood. Our data indicate that likely predisposing factors for developing TCPP include young age, a preceding history of cold intolerance and an arachnodactyloid phenotype. Anorexia, connective tissue disorders or sickle cell trait may also predispose to TCPP. In addition, low titre antinuclear antibody positivity, the presence of cryoglobulins, or low complement levels may represent further risk factors. Finally, prolonged low temperatures are also likely to be contributing to the symptoms. Abstract : We describe a series of 16 cases of COVID‐related tardive pseudoperniosis (PP). Symptoms in all patients persisted beyond 2 months. Positive autoimmune serological markers and an arachnodactyloid phenotype were observed in some patients and may represent risk factors. Underlying connective tissue disorders, anorexia or sickle cell trait may also predispose to prolonged PP.